Use of pyridazinediones as extracellular cleavable linkers through reversible cysteine conjugation. Issue 98 (25th November 2019) - Bahou, Calise; Spears, Richard J.; Aliev, Abil E.; Maruani, Antoine; Fernandez, Marcos; Javaid, Faiza; Szijj, Peter A.; Baker, James R.; Chudasama, Vijay
Abstract : Herein we report the potential use of pyridazinediones as novel extracellular cleavable linkers in the context of protein bioconjugates. Abstract : Herein we report a retro-Michael deconjugation pathway of thiol–pyridazinedione linked protein bioconjugates to provide a novel cleavable linker technology. We demonstrate that the novel pyridazinedione linker does not suffer from off-target modification with blood thiols ( e.g., glutathione, human serum albumin (HSA)), which is in sharp contrast to an analogous maleimide linker.